Non surgical management for massive gastric lipomatosis (2020)
BACKGROUND: Gastric lipomatosis (GL) is defined as a lipomatous lesion with diffuse infiltration of thesubmucosal layer by adipose tissue with multiple lesions and must be differentiated from gastroin-testinal lipomas, which are solitary submucosal masses composed of well-differentiated adipose tissuesurrounded by a fibrous capsule. GL are uncommon, represents 5 % of gastrointestinal tract lipomas andless than 1∼3 % of all gastric tumors.CASE PRESENTATION: A 65-year-old woman, who underwent non-operatively approach by Gastric lipo-matosis. Non-specific gastrointestinal symptoms and endoscopic examination ruled out the possibilityof mucosal ulceration or bleeding. Endoscopic ultrasonography and abdominal CT that confirmed gastriclipomatosis.DISCUSSION: Gastric lipomas are usually small, solitary and asymptomatic, and are hence often detectedincidentally, surgical management in asymptomatic patients still be a in debate.CONCLUSION: Non operative management in massive gastic lipomatosis is appropiate when the patient isasymptomatic without mucosal ulceration, regardless of the amount of gastric lipomas. Avoiding patientthe morbidity of a total gastrectomy.